Plasma cell neoplasm manifesting initially as a sub-cutaneous supra-orbital swelling - Riddhi Jaiswal; Garima Agarwal; Sudhir Singh (Wolters Kluwer Medknow Publications, 2016)
Multiple myeloma is a plasma cell neoplasm seen usually in patients over 50 years of age. Some cases may be asymptomatic initially and are detected during a routine test like complete blood count. They only require a close follow-up and monitoring. However, around 1% of these monoclonal gammopathy of undetermined significance progress to multiple myeloma every year and then they need to be taken care of by chemotherapy, targeted therapy, bisphosphonates and 6 monthly urine and bone examinations. Here, we present a case of 35-year-old female with an initial symptom of a vague backache along with a left subcutaneous supra-orbital swelling which was diagnosed as multiple myeloma by aspiration cytology and confirmed by ancillary tests. She has since been on treatment with bortezomib and prednisone and is responding well.